Enhanced energy storage performance of surfactant assisted grown cobalt hydroxide. (2023) - Kumar, Jitendra; Singh, Jay; Vaibhav Mishra, Vipul; Kumar Rastogi, Chandresh; Mandal, Biswajit
Abstract: The use of surfactant during synthesis process is critical in determining morphology as well as properties of nanomaterials. In this line, this work reports surfactant assisted synthesis of Co(OH)2 nanomaterials and their characterizations for energy storage applications. Cobalt hydroxide nanoparticles are synthesized using chemical co-precipitation method at 80 °C using hexamethylenetetramine (HMTA) as surfactant. The sample prepared using surfactant and without surfactant are labelled as CHHMTA and CH, respectively. Scanning electron microscopy, X-ray diffraction, and FTIR techniques were used to evaluate the structural, morphological, and elemental features of the produced products. To understand the energy storage capabilities of the collected products, cyclic voltammetry (CV) and galvanometric charge/discharge (GCD) are used. In comparison to bare Co(OH)2 nanoparticles, HMTA coated particles exhibits improved charge storage characteristics. The specific capacitance for CH and CHHMTA was determined as 127 and 344 Fg −1 at 1 Ag −1 current density, respectively.